Nafs Maturity as Foundation of Islamic Leadership, Work Behavior, and Organizational Performance - Sora Baltasar; Eka Budiandri; Yose Hernando; Donny Gumilar; Refsi Meilawati (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
This study examines how nafs maturity influences the internalization of Islamic leadership values and its implications for work behavior and organizational performance. Previous leadership and human resource management studies, including Islamic perspectives, largely emphasize structural and managerial factors, yet provide limited explanation for variations in employees’ responses to identical leadership values. Employing an analytically oriented qualitative literature review, this study synthesizes findings from reputable national and international journals in Islamic psychology, leadership, and organizational behavior. Qualitative content analysis is applied using a comparative and interpretative approach, mapping empirical findings onto the nafs typology (ammarah, lawwāmah, and muṭma’innah). The findings reveal that nafs maturity determines the depth of leadership value internalization, shaping self-control, Islamic work ethic, emotional regulation, and behavioral consistency. Higher nafs maturity is associated with deep internalization and sustainable performance, while lower maturity tends to result in formal compliance and passive resistance. This study highlights nafs maturity as a foundational internal mechanism linking Islamic leadership, work behavior, and sustainable organizational performance